To the problem of transfer clusters parametric optimizazion (Journal of Economic Research & Business Administration, 2015)
the paper proposed and investigated such models that can be used as the basis of analysis and management integration methods based on transfer pricing and implemented in their respective information systems. Transfer clusters are the result of the integration of business processes based on transfer pricing. The main tasks which are dealt with is the evaluation of effectiveness of cluster, select the effective values of transfer parameters (such as the rate of transfer, share of income of the cluster of each participant of the cluster), estimating of risks for indicators and parameters and some other.
Keywords: Clusters; transfer pricing; models; business processes; efficiency; management